No Hobo is an Island: Power and Political Culture in the Federal Work Relief Camps in British Columbia, 1932-1935 - Adolph, Neal Robert (Simon Fraser University, 2015)
This thesis explores the political experience of men in the Department of National Defence’s work relief camps in British Columbia from 1932 to 1935, when single, homeless, unemployed, and physically fit men accessed government unemployment relief living and working according to the administration’s policies. In these camps the men found a government administration eager to teach them work discipline, a collection of charities and private groups that promoted an ideal of the working class man in troubled economic times, and organizers with the Relief Camp Workers’ Union attempting to shape strikes that challenged government authority. In this thesis I argue that the unemployed vacillated between these different influences to challenge the government’s palliative relief while also ensuring that they maintained access to relief for as long as possible. This was accomplished by shaping multi-faceted relationships with the government, the union, private charities, and fellow campers.